FIBRINOGEN MILANO III, A NEW ABNORMAL HEREDITARY FIBRINOGEN VARIANT WITH A DEFECT IN THE Aα-CHAIN - Bögli, C; Hofer, A; Furlan, M; Beck, E A; Baudo, F; Redaelli, R (Thrombosis and Haemostasis, 1987)
A new congential dysfibrinogenemia, denoted as Milano III, was found in a 13-year-old girl with recurrent thrombophlebitis. Plasma of the patient exhibited prolonged thrombin and reptilase times. Plasma fibrinogen concentration, determined by a functional assay, was less than 0.2 g/1 while the immunological method revealed normal fibrinogen levels. Fibrinopeptide release, induced by thrombin, was normal whereas polymerization of fibrin monomers was delayed. Under conventional conditions for normal fibrin aggregation, with and without added calcium, the final turbidity of abnormal fibrin was léss than 10 % of normal fibrin turbidity. The abnormal fibrinogen strongly inhibited clotting of normal fibrinogen. Isoelectric focusing showed an abnormal Aα-chain with greatly increased anodic mobility suggesting that the net electric charge of the Aα-chain is similar to that of the γ-chain. SDS-PAGE as well as reversed phase HPLC of mercap-tolyzed fibrinogen showed normal Bβ- and γ-chains whereas the Aα-chain was degraded. The susceptibility towards degradation appears to be related to the molecular defect in the variant Aα-chain, since normal Aα-chain was not affected under the same conditions. Intact size of Aα-chain was preserved during preparative chromatofocusing of reduced fibrinogen chains. Fibrinogen preparations from the proposita's mother and father contained approximately equal amounts of both normal and abnormal Aα-chain. We conclude that fibrinogen Milano III in the proposita is a new homozygous functionally abnormal variant with a structural defect in the Aochain which is not located in the amino terminus.